Psychology in professional sports and the performing arts challenges and strategies - Schinke, Robert J.; Hackfort, Dieter (London Routledge, Taylor & Francis Group, 2017)
The relationship between sport and exercise psychology and the realm of professional sport and performance has grown exponentially in recent years. Elite athletes increasingly see the value in seeking psychological advice and expertise, while consultants now work in a wider range of elite performance environments. This is a unique and timely collection that brings together the experiences and knowledge of a range of applied psychologists working in these exciting industries.
Embarking on sport psychology with professional level athletes / Dieter Hackfort & Robert J. Schinke -- Context is everything : working with the transitioning athlete / Angus Mugford -- How to become a consulting business / Robert M. Nideffer -- Overcoming resistance from clients and stakeholders / Frank L. Gardner -- Working with transnational professional athletes / Zella E. Moore -- Ethical practice challenges of consultation in professional sport / Edward F. Etzel and Jack C. Watson II -- 20 years' experience working within professional tennis / Chris Harwood -- My consulting life on the PGA tour : a twenty-five year experience / Richard Gordin -- How a plant pot led me to performance psychology in women's professional golf / Christian Smith -- The strategies and methods for working with professional car racers / Dieter Hackfort -- Consultancy with elite professional boxers and their working teams / Robert J. Schinke -- Working within professional mixed martial arts / Rebecca Symes -- Mental training program for a sumo wrestler / Yoichi Kozuma -- Working within polo: a wonderland experience / Stiliano 'Ani' Chroni -- Working within the National Hockey League / Paul Dennis -- Working within professional soccer / Mark S. Nesti -- Working within Professional Rugby Union / Stephen D. Mellalieu -- Working within elite professional cricket : the role of a sport psychology consultant / Stewart T. Cotterill -- Working within professional baseball : reflections and recommendations on the practice of sport and performance psychology / Charles A. Maher -- From the sport world to the big top : Jean Francois Menard's journey with Cirque du Soleil / Leslee A. Fisher and Jean Francois Menard -- Performance psychology in ballet and modern dance / Sharon A. Chirban & Miriam R. Rowan -- My journey into sports psychology : strategies, challenges and case studies / Lois Butcher-Poffley -- Synthesis and reflections on professional sport consulting / Dieter Hackfort & Robert J. Schinke.
Includes bibliographical references and index.
Keywords: Sports -- Psychological aspects; Professional sports -- Psychological aspects; Athletes -- Psychology; Professional athletes -- Psychology; Performing arts -- Psychological aspects; Sports psychologists -- Biography